Medicago polymorpha L. forage production and its quality when grazed by ewes - Sitzia M.; Ligios S.; Fois N. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In order to assess the forage availability and the quality of Medicago polymorpha L. used on dairy sheep Mediterranean system, a research was carried out during 1998. Dry matter availability and chemical composition were measured during the grazing period. At maturity the pod production and the seed components were assessed. Average forage availability was above 1.5 t DM ha-1 in winter-spring period. Chemical composition of burr medic was characterised by a high crude protein and a low fibre fraction level. The pod production could be considered more than optimal to make a seed bank (3.1 t ha-1). These preliminary results show that burr medic is an interesting species regarding the nutrition of dairy ewes.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)